PENDAMPINGAN STRATEGI MANAJEMEN PEMASARAN TERPADU UNTUK MENINGKATKAN PENJUALAN UMKM LOKAL DI PAUH, KOTA PADANG - Wahyudi, Harry; Malik, David; Visza Adha, Howardi; Amrullah, Amrullah; Suandi, Edi; Suhanda, Mya Yuwanita (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting the local economy in Pauh District, Padang City. However, most MSMEs still face challenges in marketing management, particularly in developing and implementing well-planned, integrated, and sustainable strategies. Marketing activities tend to be conventional and sporadic, without clear planning, and without integrating offline and digital marketing. This situation results in low sales and limited market reach. This Community Service Program aims to increase sales and competitiveness of MSMEs through integrated marketing management strategy assistance. The methods used include training, hands-on practice, and ongoing assistance, emphasizing the integration of conventional and digital marketing. The activity begins with identifying partner needs, followed by training in marketing management concepts, market analysis, and developing strategies tailored to business characteristics. Partners are then assisted in implementing offline promotions, utilizing social media, and creating engaging marketing content, along with monitoring and evaluation. The expected results are increased capacity of MSMEs, the development of integrated marketing strategies, increased sales, and the strengthening of sustainable business competitiveness